Ordnungen des Nationalen und die geteilte Welt: Zur Praxis Auswärtiger Kulturpolitik als Konfliktprävention - Adam, Jens (transcript, 2018)
This analysis of the "foreign cultural politics as conflict prevention" shows how strongly the foreign cultural politics of Germany are still being structured by national systems, narratives and hierarchies.